Do antibiotics prevent infection after third molar surgery? A network meta-analysis. Issue 9 (September 2022) - Falci, S.G.M.; Galvão, E.L.; de Souza, G.M.; Fernandes, I.A.; Souza, M.R.F.; Al-Moraissi, E.A.
Abstract: The aim of this systematic review was to determine whether antibiotics, compared to placebo, can prevent infection or dry socket after third molar surgery. A systematic review and network meta-analysis (NMA) was performed following registration of the protocol (CRD42021276266). Four databases and the grey literature were searched, and papers were selected based on the PICOS question. RoB 2 and GRADE were used to evaluate the risk of bias and certainty of the evidence, respectively. The NMA was performed using Stata. Of 58 randomized clinical trials identified, 34 were included in the NMA. Patients treated with amoxicillin (relative risk (RR) 0.56, 95% confidence interval (CI) 0.38–0.84; low quality of evidence) and those treated with metronidazole (RR 0.51, 95% CI 0.31–0.84; low quality of evidence) showed a lower risk of infection and dry socket when compared to patients given a placebo. Postoperative amoxicillin (750 mg) and amoxicillin plus clavulanate (500 mg + 125 mg, or 2000 mg + 125 mg), and preoperative metronidazole (800 mg) are useful to prevent infection or dry socket when compared to placebo. The low rate of infection after third molar surgery, the correct concept of antibiotic prophylaxis, and antibiotic resistance must be taken into account when choosing to treat healthy patients undergoing third molar surgery with antibiotics.